2008
DOI: 10.1017/s0022149x08019792
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal helminths in a population of children from the Kashmir valley, India

Abstract: In any geographical area, surveys of the prevalence of intestinal helminths are necessary to suggest appropriate control measures. The aim of this study was to determine the prevalence of intestinal helminth infections in children of the Kashmir valley and to identify the risk factors. Stool samples were collected from 2256 children from rural as well as urban areas of the Kashmir valley. The samples were examined by simple smear and zinc sulphate concentration methods. Intensity of the infection was quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 19 publications
2
24
1
Order By: Relevance
“…This is contrary to few reports documented in other parts of India where helminthic preponderance was reported (Shailendra Singh Thakur and Vipin Todase, 2018;Wani et al, 2008;Awasthi and Pande, 1997).…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…This is contrary to few reports documented in other parts of India where helminthic preponderance was reported (Shailendra Singh Thakur and Vipin Todase, 2018;Wani et al, 2008;Awasthi and Pande, 1997).…”
Section: Resultscontrasting
confidence: 55%
“…The higher prevalence in this age group may be due to the high contamination of soil where children play and eat food without washing their hands and working age group over here is mainly involved in agriculture work predisposing them by contaminated soil (Wani et al, 2008;Awasthi and Pande, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of TDS in adults in this study was possibly related to a very high prevalence of gut parasites including T trichiura in Kashmir, India. 4,5 There were several differences in clinical presentation of TDS in children and adults. Children present with dominant colonic symptoms and associated malnutrition, growth retardation, and impaired cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy is that the infections with these helminths prevailed in many study groups (Ak et al, 2006;Adeoye et al, 2007;Chen et al, 2008;Menezes et al, 2008;Wani et al, 2008;Jensen et al, 2009;Morenikeji et al, 2009). A recent survey regarding the contamination of vegetables with parasitic eggs in a market in Vietnam revealed that Ascaris sp.…”
Section: Geohelminthiasismentioning
confidence: 93%